(untitled) (Economics and region, 2025)
The subject of this article is the accounting and taxation of e-commerce transactions in Ukraine. The research allowed us to determine the stages of organizing e-commerce by a business entity and propose an algorithm for its implementation. Accounting for e-commerce transactions involves reflecting the creation and functioning of an online store and settlements with customers. The procedure for accounting for the costs of creating an e-store depends on whether it is created by the company itself or by a third-party organization. Accounting for e-commerce payments depends on the form of payment (cash, non-cash, electronic money) and the method of delivery of the order. In order to ensure high-quality accounting and control over e-commerce transactions, a Form for analytical accounting of the movement of goods sold online has been proposed for implementation.